Psychological distress in older adults: associations with epigenetic markers of ageing, inflammation, and depression, and joint effects on mortality - Danmeng Lily Li; Xiaojing Xu; Allison M. Hodge; Melissa C. Southey; Graham G. Giles; Roger L. Milne; Pierre-Antoine Dugué (Brain, Behavior, & Immunity - Health)
Background: Psychological distress is associated with adverse health outcomes. We aimed to assess whether the health impacts of psychological distress could be captured by epigenetic markers of ageing, inflammation, and depression, and whether these markers and psychological distress have a synergistic association with mortality in older Australians. Methods: Blood DNA methylation data for 1146 participants (31 % females, mean age: 69 years) in the Melbourne Collaborative Cohort Study were used to calculate epigenetic markers of ageing (PCPhenoAge, PCGrimAge, bAge, DunedinPACE) and inflammation (C-reactive protein [mCRP]), and two methylation scores for depression. Psychological distress was assessed by the Kessler scale (K10). Linear regression was used to assess the associations of K10 with epigenetic markers. Cox models were used to assess the multiplicative and additive interactions of K10 and epigenetic markers in their association with all-cause mortality. Results: We observed positive associations of K10 with epigenetic markers of ageing and inflammation: per standard deviation (SD), 0.05 (95 %CI: 0.00–0.11) for DunedinPACE to 0.10 (95 %CI: 0.05–0.16) for PCPhenoAge. Associations of epigenetic markers of ageing with mortality were stronger in participants with higher psychological distress. The relative excess risk due to interaction for DunedinPACE was 0.82, 95 %CI: 0.14–1.50. Conclusion: In older Australians, higher psychological distress was associated with older epigenetic age and higher mCRP. Participants with higher levels of both psychological distress and epigenetic markers of ageing and mCRP had higher mortality risk. These findings highlight links between psychological and biological health, and the potential importance of considering both for disease risk stratification.